A kind of prefabricated building block with high porosity and light weight and high strength using all-waste materials and its preparation method

By adopting the internal air cavity high pore rate of the internal empty cavity and high -quality prefabricated blocks prepared by the use of all -empty cavity and high pore rate prepared by materials and other materials such as materials such as the full waste cement slurry and other materials, the problem of low intensity and durability of the prefabricated blocks of ceramic grains and concrete The light quality, excellent thermal insulation performance and high quality stability have been promoted to reuse the use of solid waste resources.

CN118894684BActive Publication Date: 2025-01-24INNER MONGOLIA AGRICULTURAL UNIVERSITY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411400459.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-01-24
Estimated Expiration
2044-10-09

AI Technical Summary

Technical Problem

The existing prefabricated ceramic aerated concrete blocks have low strength, strong water absorption and poor durability, making them difficult to widely use in buildings and projects that require high strength.

Method used

Adopting the preparation method of the internal empty cavity high porosity rate full waste and light -strong prefabricated blocks, through the full waste of Arnit's foam cement slurry, waste glass powder, solid sulfur ash active powder, wheat ears ash, inner empty cavity high, high cavity high cavity high cavity high cavity The combination of pore rate lightweight artificial coarse aggregate, tail mineral sand, regenerative glass fiber fiber, water reducing agent and water, and prepare light -quality pre -made blocks with high strength and good quality stability.

Benefits of technology

Realized the performance of light quality, excellent thermal insulation performance, high quality stability, and effectively eliminating a variety of low -quality solid waste materials, reducing production costs, promoting the reuse of solid waste resources, improving the mechanical performance of the block And durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118894684B_ABST
    Figure CN118894684B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of building materials, and in particular to a prefabricated building block with high porosity and high strength from all waste in an inner cavity and a preparation method thereof. According to the mass percentage, the prefabricated building block with high porosity and high strength from all waste in an inner cavity comprises 20.6 parts of all waste Alinite foamed cement slurry, 3.9 parts of waste glass powder, 3.2 parts of solid sulfur ash active powder, 1.3 parts of wheat husk ash, 34.9 parts of high porosity and light artificial coarse aggregate in the inner cavity, 24.8 parts of tailings sand fine aggregate, 8.1 parts of recycled glass fiber reinforced plastic fiber, 0.2 parts of water reducer, and 3 parts of water; the particle size of the high porosity and light artificial coarse aggregate in the inner cavity is 5-40 mm, and it comprises 20-30 parts of coal liquefaction heavy oil, 30-45 parts of fly ash, 5-10 parts of epichlorohydrin saponified waste slag powder, and 15-20 parts of coal gangue slurry below 4500 kcal. The present application provides a method for preparing a hollow, high-porosity, all-waste, lightweight, high-strength prefabricated building block to solve the problems of low strength and small production scale of artificial aggregates in related technologies.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of building materials, and in particular to an all-waste lightweight high-strength prefabricated building block with an inner cavity and high porosity, and a preparation method thereof. Background Art

[0002] Compared with traditional engineering concrete precast blocks, ceramsite aerated concrete precast blocks are lighter in weight, can effectively reduce the weight of buildings, and exhibit excellent thermal insulation performance. However, ceramsite aerated concrete precast blocks have low strength, strong water absorption and are brittle, resulting in poor durability, making them difficult to be widely used in buildings and projects that require higher strength. Therefore, in order to achieve the light weight and high strength of concrete precast blocks, it is urgent to develop a block preparation method for lightweight precast blocks with high strength and good quality stability.

[0003] At present, the utilization of solid waste in concrete is mainly achieved through powder and aggregate / aggregate. Although admixtures have been widely used in concrete, some low-quality solid waste has not been effectively utilized. Artificial aggregate is a technology that makes various solid waste powder materials into granular aggregate. At present, the production process of lightweight artificial aggregate is mainly concentrated on sintered ceramsite. Although sintered ceramsite has many technical advantages, its price is high and it is difficult to meet the requirements of structural concrete for aggregate strength, elastic modulus, construction uniformity, etc., so its application in structural concrete is relatively limited. Considering that the production of sintered ceramsite requires a sintering temperature of more than 1200°C, the energy consumption is large, and the traditional sintering process also faces certain limitations in production. In addition to high-temperature sintered aggregates, there are also cold-bonded aggregates, that is, fine particles are bonded and solidified at room temperature by cement or other types of cementitious materials. However, the main problem with cold-bonded aggregates is that a large amount of cement or other active cementitious materials is required, and the utilization rate of low-activity solid waste is low, resulting in poor overall performance of the finished product. Summary of the invention

[0004] The present application provides an inner cavity high porosity all-waste lightweight high-strength prefabricated building block and a preparation method thereof, so as to solve the problems of low strength of artificial aggregate and small production scale in the related art.

[0005] In the first aspect, a prefabricated building block with a high porosity and a total waste material, which is lightweight and high-strength, and which includes, by weight:

[0006] 20.6 parts of all-waste Alinite foamed cement slurry, 3.9 parts of waste glass powder, 3.2 parts of solid sulfur ash active powder, 1.3 parts of wheat husk ash, 34.9 parts of inner cavity high porosity lightweight artificial coarse aggregate, 24.8 parts of tailings sand fine aggregate, 8.1 parts of recycled glass fiber, 0.2 parts of water reducer, 3 parts of water, the tailings sand fine aggregate has a particle size of 0.125-2mm, the recycled glass fiber has a diameter of 0.35mm and a length of 6-14mm, and the water reducer is a polycarboxylic acid high-efficiency water reducer;

[0007] The particle size of the inner cavity high porosity lightweight artificial coarse aggregate is 5-40 mm, and it includes 20-30 parts of coal liquefaction heavy oil, 30-45 parts of fly ash, 5-10 parts of epichlorohydrin saponified waste residue powder, and 15-20 parts of coal gangue slurry below 4500 kcal.

[0008] Preferably, in terms of mass fractions, the all-waste alnitr foamed cement slurry includes 66-69 parts of all-waste alnitr cement, 1.5-3.5 parts of sodium dodecylbenzene sulfonate, 0.1-0.5 parts of amino acid surfactant, 0.2-0.5 parts of hydroxypropyl cellulose, and 28-30 parts of water.

[0009] Preferably, in terms of mass percentage, the all-waste Alinite cement includes 25-30 parts of blast furnace slag, 20-25 parts of phosphorus slag, 3-8 parts of furnace ash, 25-30 parts of fly ash, 5-10 parts of coal gangue powder, 6-9 parts of alkali slag, and 5-15 parts of desulfurized gypsum.

[0010] In a second aspect, a method for preparing an inner cavity high porosity all-waste lightweight high-strength prefabricated building block is provided, which is used to prepare an inner cavity high porosity all-waste lightweight high-strength prefabricated building block as described above, and comprises the following steps:

[0011] S1. Provide mold: clean the inside of the mold of 2000mm×1000mm×120mm, and apply mold release agent after compacting;

[0012] S2, 34.9 parts of high-porosity lightweight artificial coarse aggregate with internal cavity and 24.8 parts of tailings sand fine aggregate were placed in a mixer and stirred for 3 minutes at a speed of 120-150 r / min;

[0013] S3, preparing all-waste alinite foamed cement slurry;

[0014] S4, put 20.6 parts of all-waste Alinite foamed cement slurry, 3.9 parts of waste glass powder, 3.2 parts of fixed sulfur ash active powder, and 1.3 parts of wheat husk ash into a mixer according to the proportion and stir for 4 minutes, and the mixer speed is 120-150 r / min;

[0015] S5. Mix 0.2 parts of water reducer with 3 parts of water, add into the mixer and stir for 2 minutes at a speed of 120-150 r / min.

[0016] S6, adding 8.1 parts of recycled glass fiber into a mixer and stirring for 2 minutes at a mixer speed of 120-150 r / min; then stirring for 1 minute at a mixer speed of 250-300 r / min to obtain a lightweight concrete slurry;

[0017] S7, laying the mold flat on the ground, pouring the lightweight concrete slurry into the mold, and performing vibration treatment to obtain initial setting concrete, the vibration time is 10-15s, the amplitude is 0.1-0.5mm, and the vibration frequency is 20-50Hz;

[0018] S8. Curing the primary setting concrete: placing the primary setting concrete in an environment with a temperature of 20±2° C. and a relative humidity of 65-75% for 24 hours, then demoulding to obtain demoulding concrete, and curing the demoulding concrete for 7 days at a temperature of 20±2° C. and a relative humidity greater than 95%; after the demoulding concrete is completely solidified, curing it under natural conditions for 7 days to obtain a finished product with a high-porosity, fully-waste, lightweight, high-strength prefabricated block having a cavity.

[0019] Preferably, in S2, the method for preparing the inner cavity high porosity lightweight artificial coarse aggregate comprises the following steps:

[0020] S201, 20-30 parts of coal liquefaction heavy oil, 30-45 parts of fly ash and 5-10 parts of epichlorohydrin saponified waste residue are mixed to obtain a raw meal, and the raw meal is put into a granulator for spheroidization treatment, the granulator speed is 60-80 r / min, and raw meal balls are obtained, the fly ash particle size is 200-300 mesh, and the epichlorohydrin saponified waste residue powder particle size is 200-300 mesh;

[0021] The raw material balls with particle sizes of 5mm, 10mm, 15mm, 20mm, 25mm, 30mm and 35mm are selected to enter the next process;

[0022] S202, place 15~20 portions of coal gangue slurry below 4500 kcal in the central injection machine, and then place raw material balls with particle sizes of 5mm, 10mm, 15mm, 20mm, 25mm, 30mm, 35mm into the corresponding 10mm, 15mm, 20mm, 25mm, 30mm, 35mm, 40mm molds of the central injection machine for injection treatment:

[0023] The coal gangue slurry with a pressure of less than 4500 kcal is hydraulically injected into the raw ball by a central injection machine to obtain the injected raw ball. The injection amount of the raw ball with a particle size of 5 mm is 0.02 mL, the injection amount of the raw ball with a particle size of 10 mm is 0.15 mL, the injection amount of the raw ball with a particle size of 15 mm is 0.5 mL, the injection amount of the raw ball with a particle size of 20 mm is 1.2 mL, the injection amount of the raw ball with a particle size of 25 mm is 2.4 mL, the injection amount of the raw ball with a particle size of 30 mm is 4 mL, and the injection amount of the raw ball with a particle size of 35 mm is 5.5 mL;

[0024] Screen the injection raw material balls with particle sizes of 5mm<particle size≤10mm, 10mm<particle size≤15mm, 15mm<particle size≤20mm, 20mm<particle size≤25mm, 25mm<particle size≤30mm, 30mm<particle size≤35mm, 35mm<particle size≤40mm for standby use;

[0025] S203, placing the pressed raw material balls obtained in step S202 in a compacting machine, setting the pressure value to 0.02-0.1 MPa, and performing spherical shaping and compacting of the aggregate to obtain compacted aggregate:

[0026] The set pressure value for the pressed raw ball with a particle size of 5mm<particle size≤10mm is 0.1Mpa, the set pressure value for the pressed raw ball with a particle size of 10mm<particle size≤15mm is 0.09Mpa, the set pressure value for the pressed raw ball with a particle size of 15mm<particle size≤20mm is 0.08Mpa, the set pressure value for the pressed raw ball with a particle size of 20mm<particle size≤25mm is 0.07Mpa, the set pressure value for the pressed raw ball with a particle size of 25mm<particle size≤30mm is 0.05Mpa, the set pressure value for the pressed raw ball with a particle size of 30mm<particle size≤35mm is 0.03Mpa, and the set pressure value for the pressed raw ball with a particle size of 35mm<particle size≤40mm is 0.02Mpa;

[0027] The compacted aggregate with a particle size of 5 to 40 mm is selected and sent to the next process;

[0028] S204, placing the compacted aggregate obtained in S203 in a zoned temperature-controlled calcining device for microwave zoned multi-stage calcination:

[0029] The compacted aggregate is microwave calcined at 400°C in the first zone for 20 minutes, then the compacted aggregate is microwave calcined at 700°C in the second zone for 15 minutes, and then the compacted aggregate is microwave calcined at 1000°C in the third zone for 10 minutes to obtain a molded aggregate;

[0030] The formed aggregate is subjected to oxygen-free environment micro-carbon-fixing wind cooling to room temperature in the fourth zone of CO2 exhaust air cooling;

[0031] Finally, the formed aggregate cooled to room temperature is placed in a 32-hedron vertex passivation blister steel ball electromagnetic shell solidification device with a diameter of 5 mm, and the outer shell of the formed aggregate cooled to room temperature is continuously solidified with small force and high frequency for 5 minutes to obtain a lightweight artificial coarse aggregate with high porosity in the inner cavity.

[0032] Preferably, the particle size distribution of the manufactured inner cavity high porosity lightweight artificial coarse aggregate includes: 5 mm<particle size≤10 mm: 10~15%; 10 mm<particle size≤20 mm: 10~15%; 20 mm<particle size≤30 mm: 35~40%; 30 mm<particle size≤35 mm: 20~25%; 35 mm<particle size≤40 mm: 15%.

[0033] Preferably, the method for preparing the coal gangue slurry with a content of less than 4500 kcal comprises the following steps:

[0034] Coal gangue powder with less than 4500 kcal and water are stirred in a mixer at a mass percentage ratio of 1.5-2 for 10-15 minutes to obtain coal gangue slurry with less than 4500 kcal. The mixer speed is 500-600 r / min, and the particle size of the coal gangue powder with less than 4500 kcal is 150-200 mesh.

[0035] Preferably, the coal liquefaction heavy oil has a specific gravity of 0.85-0.9.

[0036] Preferably, in S3, the method for preparing the all-waste Alnitr foamed cement slurry comprises the following steps:

[0037] Add 28-30 parts of water into a stirring pot, dissolve 1.5-3.5 parts of sodium dodecylbenzene sulfonate in the water, add 0.1-0.5 parts of an amino acid surfactant, and stir for 5-10 minutes to obtain a solution;

[0038] The solution is placed in a mixer, and then 68-70 parts of all-waste alnit cement and 0.2-0.5 parts of hydroxypropyl cellulose are placed in the mixer and stirred for 5-10 minutes at a mixer speed of 500-600 r / min to obtain all-waste alnit foamed cement slurry.

[0039] Preferably, the method for preparing the all-waste alnit cement comprises the following steps:

[0040] Grind 25-30 parts of blast furnace slag, 20-25 parts of phosphorus slag, 3-8 parts of furnace ash, 25-30 parts of fly ash, 5-10 parts of coal gangue powder, and 6-9 parts of alkali slag, pass through a 200-mesh sieve, mix evenly, and press into a test cake of 50 mm × 5 mm;

[0041] The test cake is preheated at 800-1000° C. for 5-10 minutes, calcined at 1250-1300° C. for 40-60 minutes, and cooled to 30° C. to obtain cement clinker;

[0042] The cement clinker is mixed with 5-15 parts of desulfurized gypsum and ground to a fineness of 400-500m 2 / kg, to obtain the all-waste alinite cement.

[0043] The beneficial effects of the technical solution provided by this application include:

[0044] The present application provides an inner cavity high porosity all-waste lightweight high-strength prefabricated building block and a preparation method thereof, which has the following advantages:

[0045] The prefabricated blocks with high porosity and high strength in the inner cavity made of all-waste Alinite foamed cement slurry, waste glass powder, solid sulfur ash active powder, wheat husk ash, high porosity and light artificial coarse aggregate in the inner cavity, fine aggregate of tailings sand, recycled glass fiber, water reducer and water have the advantages of light weight, high strength, excellent thermal insulation performance and high quality stability. At the same time, the blocks can effectively absorb a variety of low-quality solid waste materials, with low cost, and promote the reuse of solid waste resources.

[0046] The application uses all-waste Alnit foamed cement slurry, which has excellent performance compared to ordinary Portland cement, significantly reduces production costs, and effectively promotes the high-value utilization of industrial solid waste, thereby achieving the goal of green and low-carbon production;

[0047] The present application adopts coal liquefaction heavy oil, fly ash, epichlorohydrin saponified waste residue powder and coal gangue slurry below 4500 kcal to prepare light artificial coarse aggregate with high porosity in the inner cavity, which not only realizes the large-scale and resource utilization of low-quality solid waste materials, but also achieves the purpose of energy conservation and waste reduction, and effectively replaces traditional light ceramsite to produce light artificial coarse aggregate with high strength and high porosity in the inner cavity;

[0048] The present application provides an inner cavity high-porosity, all-waste, lightweight, high-strength prefabricated building block, which uses an all-waste alinite foamed cement slurry including calcium aluminate and calcium silicate, and its inner cavity high-porosity, lightweight artificial coarse aggregate has silicon dioxide and aluminum oxide as main components and has obvious activity; the inner cavity high-porosity, lightweight artificial coarse aggregate can continuously release silicon and aluminum elements in the all-waste alinite foamed cement slurry, thereby promoting the formation of CASH gel, improving the microstructure of the hydration product in the interface transition zone, making it denser, thereby effectively improving the mechanical properties and durability of the building block. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0050] Figure 1 A flow chart of the method for preparing the inner cavity high porosity all-waste lightweight high-strength prefabricated building blocks provided in this application;

[0051] Figure 2 A diagram showing the steps for preparing the internal cavity high porosity all-waste lightweight high-strength prefabricated building blocks provided in this application;

[0052] Figure 3 Schematic diagram of the lightweight artificial coarse aggregate with internal cavity and high porosity provided in this application. DETAILED DESCRIPTION

[0053] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0054] See also Figures 1 to 3 As shown, the present application provides a method for preparing a hollow, high-porosity, all-waste, lightweight, high-strength prefabricated building block, which can solve the problems of low strength of artificial aggregates and small production scale in the related art. Specifically, it includes the following steps:

[0055] S1. Provide mold: clean the inside of the mold of 2000mm×1000mm×120mm, and apply mold release agent after compacting;

[0056] S2. Place 34.9 parts of internal cavity high porosity lightweight artificial coarse aggregate and 24.8 parts of tailings sand fine aggregate into a mixer and stir for 3 minutes. The mixer speed is 120-150 r / min. The particle size of the tailings sand fine aggregate is 0.125-2 mm.

[0057] The method for preparing the inner cavity high porosity lightweight artificial coarse aggregate comprises:

[0058] S201. Mix 20 to 30 parts of coal liquefaction heavy oil, 30 to 45 parts of fly ash and 5 to 10 parts of epichlorohydrin saponified waste residue to obtain raw meal, and put the raw meal into a granulator for spheroidization treatment. The granulator speed is 60 to 80 r / min to obtain raw meal balls; optionally, the fly ash particle size is 200 to 300 mesh, and the epichlorohydrin saponified waste residue powder particle size is 200 to 300 mesh.

[0059] The raw material balls with particle sizes of 5mm, 10mm, 15mm, 20mm, 25mm, 30mm and 35mm are selected to enter the next process;

[0060] S202, place 15~20 portions of coal gangue slurry below 4500 kcal in the central injection machine, and then place raw material balls with particle sizes of 5mm, 10mm, 15mm, 20mm, 25mm, 30mm, 35mm into the corresponding 10mm, 15mm, 20mm, 25mm, 30mm, 35mm, 40mm molds of the central injection machine for injection treatment:

[0061] The coal gangue slurry with a pressure of less than 4500 kcal is hydraulically injected into the raw ball by a central injection machine to obtain the injected raw ball. The injection amount of the raw ball with a particle size of 5 mm is 0.02 mL, the injection amount of the raw ball with a particle size of 10 mm is 0.15 mL, the injection amount of the raw ball with a particle size of 15 mm is 0.5 mL, the injection amount of the raw ball with a particle size of 20 mm is 1.2 mL, the injection amount of the raw ball with a particle size of 25 mm is 2.4 mL, the injection amount of the raw ball with a particle size of 30 mm is 4 mL, and the injection amount of the raw ball with a particle size of 35 mm is 5.5 mL;

[0062] Screen the injection raw material balls with particle sizes of 5mm<particle size≤10mm, 10mm<particle size≤15mm, 15mm<particle size≤20mm, 20mm<particle size≤25mm, 25mm<particle size≤30mm, 30mm<particle size≤35mm, 35mm<particle size≤40mm for standby use;

[0063] S203, placing the injected raw material balls obtained in step S202 in a compacting machine, setting the pressure value to 0.02-0.1 MPa, and performing spherical shaping and compacting of the aggregate to obtain compacted aggregate:

[0064] The set pressure value for the pressed raw ball with a particle size of 5mm<particle size≤10mm is 0.1Mpa, the set pressure value for the pressed raw ball with a particle size of 10mm<particle size≤15mm is 0.09Mpa, the set pressure value for the pressed raw ball with a particle size of 15mm<particle size≤20mm is 0.08Mpa, the set pressure value for the pressed raw ball with a particle size of 20mm<particle size≤25mm is 0.07Mpa, the set pressure value for the pressed raw ball with a particle size of 25mm<particle size≤30mm is 0.05Mpa, the set pressure value for the pressed raw ball with a particle size of 30mm<particle size≤35mm is 0.03Mpa, and the set pressure value for the pressed raw ball with a particle size of 35mm<particle size≤40mm is 0.02Mpa;

[0065] The compacted aggregate with a particle size of 5 to 40 mm is selected and sent to the next process;

[0066] S204, placing the compacted aggregate obtained in S203 in a zoned temperature-controlled calcining device for microwave zoned multi-stage calcination:

[0067] The compacted aggregate is microwave calcined at 400°C in the first zone for 20 minutes, then the compacted aggregate is microwave calcined at 700°C in the second zone for 15 minutes, and then the compacted aggregate is microwave calcined at 1000°C in the third zone for 10 minutes to obtain a molded aggregate;

[0068] The formed aggregate is subjected to oxygen-free environment micro-carbon-fixing wind cooling to room temperature in the fourth zone of CO2 exhaust air cooling;

[0069] Finally, the molded aggregate cooled to room temperature is placed in a 32-hedron vertex passivated blister steel ball electromagnetic shell solidification device with a diameter of 5 mm, and the outer shell of the molded aggregate cooled to room temperature is continuously solidified with small force and high frequency for 5 minutes, and the surface of the aggregate is secondary solidified to obtain a lightweight artificial coarse aggregate with high porosity in the inner cavity.

[0070] In some embodiments, the particle size distribution of the manufactured internal cavity high porosity lightweight artificial coarse aggregate includes: 5 mm<particle size≤10 mm: 10~15%; 10 mm<particle size≤20 mm: 10~15%; 20 mm<particle size≤30 mm: 35~40%; 30 mm<particle size≤35 mm: 20~25%; 35 mm<particle size≤40 mm: 15%.

[0071] The raw material ball aggregate is treated by injecting coal gangue slurry below 4500 kcal, combined with aggregate spherical shaping and compaction to obtain spherical aggregate; then low-temperature microwave calcination is carried out to stimulate the activity of fly ash and achieve hydration flash condensation, medium-temperature microwave calcination promotes continuous hydration and rapid dehydration, and high-temperature microwave calcination induces carbon decomposition of coal gangue slurry at high temperature, forming internal cavities and external high porosity of aggregate, and achieving calcination molding. Finally, micro-carbon-fixing air cooling is carried out in an oxygen-free environment with CO2 exhaust gas air cooling to maintain the activity of aggregate and achieve effective solidification. Subsequently, the aggregate shell is continuously knocked with low force and high frequency by the electromagnetic shell solidification device of the 32-faceted vertex passivated blister steel ball with a diameter of 5mm to remove the debris and protrusions on the aggregate surface and achieve secondary solidification of the aggregate surface. This method not only realizes the large-scale and resource utilization of low-quality solid waste materials and achieves the purpose of energy conservation and waste reduction, but also effectively replaces traditional lightweight expanded clay and produces lightweight artificial coarse aggregate with high strength and high internal cavity porosity.

[0072] In some embodiments, the method for preparing the coal gangue slurry with a content of less than 4500 kcal comprises the following steps:

[0073] The coal gangue powder with a mass percentage of less than 4500 kcal and water are stirred in a mixer at a ratio of 1.5 to 2 by mass for 10 to 15 minutes to obtain a coal gangue slurry with a mass percentage of less than 4500 kcal. The mixer speed is 500 to 600 r / min.

[0074] Optionally, the particle size of the coal gangue powder below 4500 kcal is 150-200 mesh.

[0075] In some embodiments, the coal liquefaction heavy oil has a specific gravity of 0.85-0.9.

[0076] S3, preparation of all-waste Alnit foamed cement slurry:

[0077] Add 28-30 parts of water into a stirring pot, dissolve 1.5-3.5 parts of sodium dodecylbenzene sulfonate in the water, add 0.1-0.5 parts of an amino acid surfactant, and stir for 5-10 minutes to obtain a solution;

[0078] The solution is placed in a mixer, and then 68-70 parts of all-waste alnit cement and 0.2-0.5 parts of hydroxypropyl cellulose are placed in the mixer and stirred for 5-10 minutes at a mixer speed of 500-600 r / min to obtain all-waste alnit foamed cement slurry.

[0079] Furthermore, the method for preparing the all-waste alnit cement comprises the following steps:

[0080] Grind 25-30 parts of blast furnace slag, 20-25 parts of phosphorus slag, 3-8 parts of furnace ash, 25-30 parts of fly ash, 5-10 parts of coal gangue powder, and 6-9 parts of alkali slag, pass through a 200-mesh sieve, mix evenly, and press into a test cake of 50 mm × 5 mm;

[0081] The test cake is preheated at 800-1000° C. for 5-10 minutes, calcined at 1250-1300° C. for 40-60 minutes, and cooled to 30° C. to obtain cement clinker;

[0082] The cement clinker is mixed with 5-15 parts of desulfurized gypsum and ground to a fineness of 400-500m 2 / kg, to obtain the all-waste alinite cement.

[0083] Specifically, the CaO content in the all-waste alinite cement is 59% to 64%, the SiO2 content is 20% to 24%, the Al2O3 content is 4% to 6%, the Fe2O3 content is 2% to 4%, the MgO2 content is 2% to 5%, and the Cl ~ The content is 1%~3%.

[0084] Furthermore, in the cement clinker, the CaO content in blast furnace slag is 34.7%, the SiO2 content is 44.9%, and the loss on ignition is 4.4%; the CaO content in phosphorus slag is 51.2%, the SiO2 content is 42.3%, and the loss on ignition is 2.73%; the SiO2 content in furnace ash is 50.71%, and the loss on ignition is 9.67%; the SiO2 content in fly ash is 45.3%, the loss on ignition is 2.25%, and the Al2O3 content is 49.2%; the CaCl2 content in alkali slag is 8.3%; the SO3 content in desulfurized gypsum is 42.74%, and the loss on ignition is 2.31%.

[0085] In this step, the all-waste alinite foamed cement slurry prepared by using all-waste alinite cement, sodium dodecylbenzene sulfonate, amino acid surfactant, hydroxypropyl cellulose, and water, wherein the raw materials of all-waste alinite cement are all industrial solid waste materials, which are excellent in performance compared to ordinary silicate cement, significantly reduce production costs, and effectively promote the high-value utilization of industrial solid waste, thereby achieving the goal of green and low-carbon production; sodium dodecylbenzene sulfonate has excellent foaming performance, and by reducing the surface tension of the liquid, the air is easily wrapped in the liquid, thereby forming a stable foam; the addition of amino acid surfactant can form a stable interfacial film, reduce the rupture and shrinkage of the foam, thereby extending the service life of the foam and further improving the stability of the foam. At the same time, it improves the fluidity of the slurry, promotes the dispersion effect of other additives, and has a lower environmental impact, and is a preferred sustainable material; hydroxypropyl cellulose can enhance the mechanical properties of the slurry, improve strength and toughness, and improve the water retention of the slurry.

[0086] S4, placing all waste Alnit foamed cement slurry, waste glass powder, fixed sulfur ash active powder, and wheat husk ash in a mixer according to the proportion and stirring for 4 minutes, with the mixer speed being 120-150 r / min;

[0087] S5. After mixing 0.2 parts of water reducer with 3 parts of water, add the mixture into a mixer and stir for 2 minutes at a mixer speed of 120-150 r / min. The water reducer is a polycarboxylate high-efficiency water reducer.

[0088] S6, adding 8.1 parts of recycled glass fiber to a mixer and stirring for 2 minutes, the mixer speed is 120-150 r / min; then stirring for 1 minute, the mixer speed is 250-300 r / min, to obtain a lightweight concrete slurry, wherein the glass fiber has a diameter of 0.35 mm and a length of 6-14 mm;

[0089] S7, laying the mold flat on the ground, pouring the lightweight concrete slurry into the mold, and performing vibration treatment to obtain initial setting concrete, the vibration time is 10-15s, the amplitude is 0.1-0.5mm, and the vibration frequency is 20-50Hz;

[0090] S8. Curing the primary setting concrete: placing the primary setting concrete in an environment with a temperature of 20±2° C. and a relative humidity of 65-75% for 24 hours, then demoulding to obtain demoulding concrete, and curing the demoulding concrete for 7 days at a temperature of 20±2° C. and a relative humidity greater than 95%; after the demoulding concrete is completely solidified, curing it under natural conditions for 7 days to obtain a finished product with a high-porosity, fully-waste, lightweight, high-strength prefabricated block having a cavity.

[0091] Specifically, in the method for preparing prefabricated blocks provided in the present application, the materials used to prepare the all-waste Alinite foamed cement slurry are all solid waste, green and environmentally friendly materials, and have excellent performance, high strength, rapid hardening, excellent thermal insulation performance, and excellent durability and corrosion resistance. Waste glass powder can fill the pores in concrete, improve the strength and working performance of concrete, solid sulfur ash active powder can effectively improve the concrete's resistance to sulfate erosion and freeze-thaw cycles; wheat husk ash can effectively improve the fluidity and slump of concrete mixtures;

[0092] The prepared artificial coarse aggregate with internal hollow cavity and high porosity has internal hollow cavity, high external porosity, light weight and high strength, and good particle size. It can absorb a variety of low-quality solid wastes on a large scale and has good economic and ecological benefits. The tailings sand fine aggregate has low cost and can improve the strength and durability of concrete, which helps to reduce the pollution of tailings accumulation to the environment. The recycled glass fiber can significantly improve the compressive strength, flexural strength, toughness, fluidity and durability of concrete. The use of water reducer can significantly improve fluidity and reduce the water-cement ratio, thereby enhancing the strength and durability of concrete, improving the construction performance of concrete, and reducing shrinkage and cracks of concrete.

[0093] Example 1

[0094] The method for preparing the inner cavity high porosity all-waste lightweight high-strength prefabricated building block provided in the present application comprises the following steps:

[0095] S1. Provide mold: clean the inside of the mold of 2000mm×1000mm×120mm, and apply mold release agent after compacting;

[0096] S2. Place 34.9 parts of inner cavity high porosity lightweight artificial coarse aggregate and 24.8 parts of tailings sand fine aggregate into a mixer and stir for 3 minutes. The mixer speed is 120 r / min. The particle size of the tailings sand fine aggregate is 0.125 mm.

[0097] The particle size of the inner cavity high porosity lightweight artificial coarse aggregate is 5-40 mm, and a two-level grading is adopted. The raw materials are shown in Table 1.

[0098] Table 1

[0099]

[0100] In this embodiment, the method for preparing the lightweight artificial coarse aggregate with inner cavity and high porosity comprises the following steps:

[0101] S201, 30 parts of coal liquefaction heavy oil, 45 parts of fly ash and 8 parts of epichlorohydrin saponification waste residue are mixed to obtain a raw meal, and the raw meal is put into a granulator for spheroidization treatment, the granulator speed is 60 r / min, and raw meal balls are obtained, the coal liquefaction heavy oil has a specific gravity of 0.85, the fly ash particle size is 200 mesh, and the epichlorohydrin saponification waste residue powder has a particle size of 200 mesh;

[0102] The raw material balls with particle sizes of 5mm, 10mm, 15mm, 20mm, 25mm, 30mm and 35mm are selected to enter the next process;

[0103] S202, place 20 portions of coal gangue slurry below 4500 kcal in the central injection machine, and then place raw material balls with particle sizes of 5mm, 10mm, 15mm, 20mm, 25mm, 30mm, and 35mm into the corresponding 10mm, 15mm, 20mm, 25mm, 30mm, 35mm, and 40mm molds of the central injection machine for injection treatment:

[0104] The coal gangue slurry with a pressure of less than 4500 kcal is hydraulically injected into the raw ball through a central injection machine. The injection amount of the raw ball with a particle size of 5 mm is 0.02 mL, the injection amount of the raw ball with a particle size of 10 mm is 0.15 mL, the injection amount of the raw ball with a particle size of 15 mm is 0.5 mL, the injection amount of the raw ball with a particle size of 20 mm is 1.2 mL, the injection amount of the raw ball with a particle size of 25 mm is 2.4 mL, the injection amount of the raw ball with a particle size of 30 mm is 4 mL, and the injection amount of the raw ball with a particle size of 35 mm is 5.5 mL;

[0105] Screen the raw balls with particle sizes of 5mm<particle size≤10mm, 10mm<particle size≤15mm, 15mm<particle size≤20mm, 20mm<particle size≤25mm, 25mm<particle size≤30mm, 30mm<particle size≤35mm, 35mm<particle size≤40mm for standby use;

[0106] S203, placing the raw material balls obtained in step S202 in a compacting machine, setting the pressure value to 0.02-0.1 MPa, and performing aggregate spherical shaping and compacting treatment:

[0107] The set pressure value of raw balls with a particle size of 5mm<particle size≤10mm is 0.1Mpa, the set pressure value of raw balls with a particle size of 10mm<particle size≤15mm is 0.09Mpa, the set pressure value of raw balls with a particle size of 15mm<particle size≤20mm is 0.08Mpa, the set pressure value of raw balls with a particle size of 20mm<particle size≤25mm is 0.07Mpa, the set pressure value of raw balls with a particle size of 25mm<particle size≤30mm is 0.05Mpa, the set pressure value of raw balls with a particle size of 30mm<particle size≤35mm is 0.03Mpa, and the set pressure value of raw balls with a particle size of 35mm<particle size≤40mm is 0.02Mpa;

[0108] The aggregate after compaction treatment with a particle size of 5 to 40 mm is selected and sent to the next process;

[0109] S204, placing the aggregate after compaction treatment in S203 in a zoned temperature-controlled calcining device for microwave zoned multi-stage calcination:

[0110] The aggregate is microwave calcined at 400°C in the first zone for 20 minutes, then the aggregate is microwave calcined at 700°C in the second zone for 15 minutes, and then the aggregate is microwave calcined at 1000°C in the third zone for 10 minutes to obtain a molded aggregate;

[0111] The formed aggregate is subjected to oxygen-free environment micro-carbon-fixing wind cooling to room temperature in the fourth zone of CO2 exhaust air cooling;

[0112] Finally, the aggregate was placed in an electromagnetic shell solidification device with a 5 mm diameter 32-sided vertex passivated blister steel ball, and the outer shell of the aggregate was continuously solidified with a small force and high frequency for 5 minutes, and the surface of the aggregate was secondary solidified, thereby obtaining a lightweight artificial coarse aggregate with high porosity in the inner cavity.

[0113] The method for preparing the coal gangue slurry with a content of less than 4500 kcal comprises the following steps:

[0114] Coal gangue powder with less than 4500 kcal and water are stirred in a mixer at a mass percentage of 1.5 for 10 minutes to obtain coal gangue slurry with less than 4500 kcal. The mixer speed is 520 r / min, and the particle size of the coal gangue powder with less than 4500 kcal is 150 mesh.

[0115] S3, preparation of all-waste Alnit foamed cement slurry:

[0116] Specifically, the raw materials for preparing the all-waste Alinite foamed cement slurry are shown in Table 2.

[0117] Table 2

[0118]

[0119] SDBS is sodium dodecylbenzene sulfonate.

[0120] Add 28 parts of water into a stirring pot, dissolve 3.5 parts of sodium dodecylbenzene sulfonate in the water, add 0.5 parts of an amino acid surfactant, and stir for 5 minutes to obtain a solution;

[0121] The solution was placed in a mixer, and then 67.7 parts of all-waste alnit cement and 0.3 parts of hydroxypropyl cellulose were placed in the mixer and stirred for 10 minutes at a mixer speed of 500 r / min to obtain all-waste alnit foamed cement slurry.

[0122] The raw materials for preparing the all-waste alnit cement are shown in Table 3.

[0123] Table 3

[0124]

[0125] The method for preparing the all-waste alnit cement comprises the following steps:

[0126] 25 parts of blast furnace slag, 20 parts of phosphorus slag, 3 parts of furnace ash, 25 parts of fly ash, 5 parts of coal gangue powder, and 6 parts of alkali slag were ground, passed through a 200-mesh sieve, mixed evenly, and pressed into a test cake of 50 mm × 5 mm;

[0127] The test cake was preheated at 800° C. for 10 min, calcined at 1250° C. for 60 min, and cooled to 30° C. to obtain cement clinker;

[0128] The cement clinker is mixed with 5 parts of desulfurized gypsum and ground to a fineness of 500 m 2 / kg, to obtain the all-waste alinite cement.

[0129] In the cement clinker, the CaO content in blast furnace slag is 34.7%; the SiO2 content is 44.9% and the loss on ignition is 4.4%. The CaO content in phosphorus slag is 51.2%; the SiO2 content is 42.3% and the loss on ignition is 2.73%; the SiO2 content in furnace ash is 50.71% and the loss on ignition is 9.67%; the SiO2 content in fly ash is 45.3% and the loss on ignition is 2.25%; the Al2O3 content is 49.2%. The CaCl2 content in alkali slag is 8.3%; the SO3 content in desulfurized gypsum is 42.74% and the loss on ignition is 2.31%.

[0130] S4, put 20.6 parts of all-waste Alinite foamed cement slurry, 3.9 parts of waste glass powder, 3.2 parts of fixed sulfur ash active powder, and 1.3 parts of wheat husk ash into a mixer according to the proportion, and stir at a speed of 120 r / min for 4 minutes;

[0131] S5. Mix 0.2 parts of polycarboxylate superplasticizer with 3 parts of water, add into a mixer, and stir at a speed of 120 r / min for 2 minutes;

[0132] S6, adding 8.1 parts of recycled glass fiber into a mixer, stirring at a speed of 120 r / min for 2 min, and then stirring at a speed of 250 r / min for 1 min to obtain a lightweight concrete slurry, wherein the recycled glass fiber has a diameter of 0.35 mm and a length of 6 mm;

[0133] S7, laying the mold flat on the ground, pouring the lightweight concrete slurry into the mold, and performing vibration treatment to obtain initial setting concrete, the vibration time is 10s, the amplitude is 0.5mm, and the vibration frequency is 20Hz;

[0134] S8. Curing the primary setting concrete: placing the primary setting concrete in an environment with a temperature of 20±2° C. and a relative humidity of 65-75% for 24 hours and then demolding to obtain demolded concrete; curing the demolded concrete for 7 days at a temperature of 20±2° C. and a relative humidity greater than 95%; after the demolded concrete is completely solidified, curing it under natural conditions for 7 days to obtain a finished product with a high-porosity, fully-waste, lightweight, high-strength prefabricated block having a cavity.

[0135] Example 2

[0136] The method for preparing the inner cavity high porosity all-waste lightweight high-strength prefabricated building block provided in the present application comprises the following steps:

[0137] S1. Provide mold: clean the inside of the mold of 2000mm×1000mm×120mm, and apply mold release agent after compacting;

[0138] S2. Place 34.9 parts of inner cavity high porosity lightweight artificial coarse aggregate and 24.8 parts of tailings sand fine aggregate into a mixer and stir for 3 minutes. The mixer speed is 150 r / min. The particle size of the tailings sand fine aggregate is 0.5 mm.

[0139] The particle size of the inner cavity high porosity lightweight artificial coarse aggregate is 5-40 mm, and a two-level grading is adopted. The raw materials are shown in Table 4.

[0140] Table 4

[0141]

[0142] In this embodiment, the method for preparing the lightweight artificial coarse aggregate with inner cavity and high porosity comprises the following steps:

[0143] S201, 27 parts of coal liquefaction heavy oil, 40 parts of fly ash and 10 parts of epichlorohydrin saponification waste residue are mixed to obtain raw material, and the raw material is put into a granulator for spheroidization treatment, and the granulator speed is 70 r / min to obtain raw material balls, wherein the coal liquefaction heavy oil has a specific gravity of 0.87, the fly ash particle size is 250 mesh, and the epichlorohydrin saponification waste residue powder has a particle size of 250 mesh;

[0144] The raw material balls with particle sizes of 5mm, 10mm, 15mm, 20mm, 25mm, 30mm and 35mm are selected to enter the next process;

[0145] S202, put 18 parts of coal gangue slurry below 4500 kcal into the central injection machine, and then put the raw material balls with particle sizes of 5mm, 10mm, 15mm, 20mm, 25mm, 30mm, 35mm into the corresponding 10mm, 15mm, 20mm, 25mm, 30mm, 35mm, 40mm molds of the central injection machine for injection treatment:

[0146] The coal gangue slurry with a pressure of less than 4500 kcal is hydraulically injected into the raw ball through a central injection machine. The injection amount of the raw ball with a particle size of 5 mm is 0.02 mL, the injection amount of the raw ball with a particle size of 10 mm is 0.15 mL, the injection amount of the raw ball with a particle size of 15 mm is 0.5 mL, the injection amount of the raw ball with a particle size of 20 mm is 1.2 mL, the injection amount of the raw ball with a particle size of 25 mm is 2.4 mL, the injection amount of the raw ball with a particle size of 30 mm is 4 mL, and the injection amount of the raw ball with a particle size of 35 mm is 5.5 mL;

[0147] Screen the raw balls with particle sizes of 5mm<particle size≤10mm, 10mm<particle size≤15mm, 15mm<particle size≤20mm, 20mm<particle size≤25mm, 25mm<particle size≤30mm, 30mm<particle size≤35mm, 35mm<particle size≤40mm for standby use;

[0148] Steps S203 and S204 are the same as those in Example 1.

[0149] The preparation method of the coal gangue slurry with a content of less than 4500 kcal comprises the following steps:

[0150] Coal gangue powder with less than 4500 kcal and water are stirred in a mixer at a mass percentage of 1.8 for 15 minutes to obtain coal gangue slurry with less than 4500 kcal. The mixer speed is 500 r / min, and the particle size of the coal gangue powder with less than 4500 kcal is 180 mesh.

[0151] S3, preparation of all-waste Alnit foamed cement slurry:

[0152] Specifically, the raw materials for preparing the all-waste Alinite foamed cement slurry are shown in Table 5.

[0153] Table 5

[0154]

[0155] SDBS is sodium dodecylbenzene sulfonate.

[0156] Add 29.5 parts of water into a stirring pot, dissolve 3.2 parts of sodium dodecylbenzene sulfonate in the water, add 0.3 parts of an amino acid surfactant, and stir for 10 minutes to obtain a solution;

[0157] The solution was placed in a mixer, and then 66 parts of all-waste alnit cement and 0.3 parts of hydroxypropyl cellulose were placed in the mixer and stirred for 8 minutes at a mixer speed of 550 r / min to obtain all-waste alnit foamed cement slurry.

[0158] The raw materials for preparing the all-waste Alinite cement are shown in Table 6.

[0159] Table 6

[0160]

[0161] The method for preparing the all-waste alnit cement comprises the following steps:

[0162] 25.5 parts of blast furnace slag, 21.6 parts of phosphorus slag, 3.2 parts of furnace ash, 26.7 parts of fly ash, 7.1 parts of coal gangue powder, and 7.9 parts of alkali slag were ground, passed through a 200-mesh sieve, mixed evenly, and pressed into a test cake of 50 mm×5 mm;

[0163] The test cake was preheated at 900°C for 7 minutes, calcined at 1260°C for 45 minutes, and cooled to 30°C to obtain cement clinker;

[0164] The cement clinker is mixed with 8 parts of desulfurized gypsum and ground to a fineness of 500 m 2 / kg, to obtain the all-waste alinite cement.

[0165] S4, put 20.6 parts of all-waste Alinite foamed cement slurry, 3.9 parts of waste glass powder, 3.2 parts of fixed sulfur ash active powder, and 1.3 parts of wheat husk ash into a mixer according to the proportion, and stir at a speed of 130 r / min for 4 minutes;

[0166] S5. Mix 0.2 parts of polycarboxylate superplasticizer with 3 parts of water, add into a mixer and stir for 2 minutes at a speed of 130 r / min.

[0167] S6, adding 8.1 parts of regenerated glass fiber into a mixer and stirring for 2 minutes at a mixer speed of 130 r / min; then stirring for 1 minute at a mixer speed of 270 r / min to obtain a lightweight concrete slurry, wherein the regenerated glass fiber has a diameter of 0.35 mm and a length of 10 mm;

[0168] S7, laying the mold flat on the ground, pouring the lightweight concrete slurry into the mold, and performing vibration treatment to obtain initial setting concrete, the vibration time is 12s, the amplitude is 0.2mm, and the vibration frequency is 30Hz;

[0169] Step S8 is consistent with that in Embodiment 1.

[0170] Example 3

[0171] The method for preparing the inner cavity high porosity all-waste lightweight high-strength prefabricated building block provided in the present application comprises the following steps:

[0172] S1. Provide mold: clean the inside of the mold of 2000mm×1000mm×120mm, and apply mold release agent after compacting;

[0173] S2. Place 34.9 parts of inner cavity high porosity lightweight artificial coarse aggregate and 24.8 parts of tailings sand fine aggregate into a mixer and stir for 3 minutes. The mixer speed is 130 r / min. The particle size of the tailings sand fine aggregate is 2 mm.

[0174] The particle size of the inner cavity high porosity lightweight artificial coarse aggregate is 5-40 mm, and a two-level grading is adopted. The raw materials are shown in Table 7.

[0175] Table 7

[0176]

[0177] In this embodiment, the method for preparing the inner cavity high porosity lightweight artificial coarse aggregate comprises:

[0178] S201, 20 parts of coal liquefaction heavy oil, 30 parts of fly ash and 5 parts of epichlorohydrin saponification waste residue are mixed to obtain a raw meal, and the raw meal is put into a granulator for spheroidization treatment, and the granulator speed is 80 r / min to obtain raw meal balls, wherein the coal liquefaction heavy oil has a specific gravity of 0.9, the fly ash particle size is 300 mesh, and the epichlorohydrin saponification waste residue powder has a particle size of 300 mesh;

[0179] The raw material balls with particle sizes of 5mm, 10mm, 15mm, 20mm, 25mm, 30mm and 35mm are selected to enter the next process;

[0180] S202. Place 15 portions of coal gangue slurry with a capacity of less than 4500 kcal in a central injection molding machine, and then place raw material balls with particle sizes of 5mm, 10mm, 15mm, 20mm, 25mm, 30mm, and 35mm into the corresponding 10mm, 15mm, 20mm, 25mm, 30mm, 35mm, and 40mm molds of the central injection molding machine for injection molding:

[0181] The coal gangue slurry with a pressure of less than 4500 kcal is hydraulically injected into the raw ball through a central injection machine. The injection amount of the raw ball with a particle size of 5 mm is 0.02 mL, the injection amount of the raw ball with a particle size of 10 mm is 0.15 mL, the injection amount of the raw ball with a particle size of 15 mm is 0.5 mL, the injection amount of the raw ball with a particle size of 20 mm is 1.2 mL, the injection amount of the raw ball with a particle size of 25 mm is 2.4 mL, the injection amount of the raw ball with a particle size of 30 mm is 4 mL, and the injection amount of the raw ball with a particle size of 35 mm is 5.5 mL;

[0182] Screen the raw balls with particle sizes of 5mm<particle size≤10mm, 10mm<particle size≤15mm, 15mm<particle size≤20mm, 20mm<particle size≤25mm, 25mm<particle size≤30mm, 30mm<particle size≤35mm, 35mm<particle size≤40mm for standby use;

[0183] Steps S203 and S204 are the same as those in Example 1.

[0184] The preparation method of the coal gangue slurry with a content of less than 4500 kcal comprises the following steps:

[0185] Coal gangue powder with less than 4500 kcal and water are stirred in a mixer at a mass percentage of 2 for 12 minutes to obtain coal gangue slurry with less than 4500 kcal. The mixer speed is 600 r / min, and the particle size of the coal gangue powder with less than 4500 kcal is 200 mesh.

[0186] S3, preparation of all-waste Alnit foamed cement slurry:

[0187] Specifically, the raw materials for preparing the all-waste Alinite foamed cement slurry are shown in Table 8.

[0188] Table 8

[0189]

[0190] SDBS is sodium dodecylbenzene sulfonate.

[0191] Add 30 parts of water into a stirring pot, dissolve 1.5 parts of sodium dodecylbenzene sulfonate in the water, add 0.1 parts of an amino acid surfactant, and stir for 8 minutes to obtain a solution;

[0192] The solution was placed in a mixer, and then 69 parts of all-waste alnit cement and 0.5 parts of hydroxypropyl cellulose were placed in the mixer and stirred for 5 minutes at a mixer speed of 600 r / min to obtain all-waste alnit foamed cement slurry.

[0193] The raw materials for preparing the all-waste Alinite cement are shown in Table 9.

[0194] Table 9

[0195]

[0196] The method for preparing the all-waste alnit cement comprises the following steps:

[0197] 30 parts of blast furnace slag, 25 parts of phosphorus slag, 8 parts of furnace ash, 30 parts of fly ash, 10 parts of coal gangue powder, and 9 parts of alkali slag were ground, passed through a 200-mesh sieve, mixed evenly, and pressed into a test cake of 50 mm × 5 mm;

[0198] The test cake was preheated at 1000° C. for 5 min, calcined at 1300° C. for 40 min, and cooled to 30° C. to obtain cement clinker;

[0199] The cement clinker is mixed with 15 parts of desulfurized gypsum and ground to a fineness of 450 m 2 / kg, to obtain the all-waste alinite cement.

[0200] S4, put 20.6 parts of all-waste Alinite foamed cement slurry, 3.9 parts of waste glass powder, 3.2 parts of fixed sulfur ash active powder, and 1.3 parts of wheat husk ash into a mixer according to the proportion, and stir at a speed of 150 r / min for 4 minutes;

[0201] S5. Mix 0.2 parts of polycarboxylate superplasticizer with 3 parts of water, add into a mixer and stir for 2 minutes at a speed of 150 r / min.

[0202] S6, adding 8.1 parts of recycled glass fiber into a mixer, stirring at a speed of 150 r / min for 2 min, and then stirring at a speed of 300 r / min for 1 min to obtain a lightweight concrete slurry, wherein the recycled glass fiber has a diameter of 0.35 mm and a length of 14 mm;

[0203] S7, laying the mold flat on the ground, pouring the lightweight concrete slurry into the mold, and performing vibration treatment to obtain initial setting concrete, the vibration time is 15s, the amplitude is 0.1mm, and the vibration frequency is 50Hz;

[0204] Step S8 is consistent with that in Embodiment 1.

[0205] Comparative Example 1

[0206] There are the following differences between Comparative Example 1 and Example 1: the only difference is that in Comparative Example 1, the use of the inner cavity high porosity lightweight artificial coarse aggregate is cancelled, and ceramsite artificial coarse aggregate is used accordingly, and the mass percentage is consistent with the cancelled component (inner cavity high porosity lightweight artificial coarse aggregate), and the remaining steps are exactly the same in Comparative Example 1 and Example 1.

[0207] That is, in step S2, the inner cavity high porosity lightweight artificial coarse aggregate is replaced with ceramsite artificial coarse aggregate.

[0208] Comparative Example 2

[0209] There are the following differences between Comparative Example 2 and Example 1: The only difference is that in Comparative Example 2, the use of waste glass powder and solid sulfur ash active powder is eliminated, and the mass percentage of all-waste Alinite foamed cement slurry is increased accordingly to replace the eliminated components, and the remaining steps are exactly the same as in Example 1.

[0210] Comparative Example 3

[0211] There are the following differences between Comparative Example 3 and Example 1: The only difference is that in Comparative Example 3, the use of wheat husk ash and recycled fiberglass fiber is eliminated, and the mass percentage of all-waste Alinite foamed cement slurry is increased accordingly to replace the eliminated components, and the remaining steps are exactly the same as in Example 1.

[0212] Specifically, the present application tests the compressive strength, flexural strength and thermal conductivity of the inner cavity high-porosity all-waste lightweight high-strength prefabricated building blocks obtained by the preparation methods provided in Examples 1 to 3 and Comparative Examples 1 to 3, and the results are shown in Table 10.

[0213] Table 10

[0214]

[0215] The inner cavity high porosity all-waste lightweight high-strength prefabricated building blocks prepared in the embodiments of the present application utilize a variety of solid waste materials, promote the high-value utilization of industrial solid waste, and reduce production costs. The prepared inner cavity high porosity lightweight artificial coarse aggregate can continuously release silicon and aluminum elements in the all-waste Alinite foamed cement slurry, thereby promoting the formation of CASH gel, improving the microstructure of the hydration product in the interface transition zone, making it denser, thereby effectively improving the mechanical properties and durability of the building blocks; at the same time, the preparation method also includes preparing all-waste Alinite foamed cement slurry, and the obtained cement slurry has low hydration heat, high strength, excellent performance and stable foaming effect, which is combined with the artificial aggregate provided by the present application to effectively improve the strength of the building blocks; as can be seen from Table 10, compared with Comparative Examples 1 to 3, Examples 1 to 3 have higher compressive strength, flexural strength and thermal conductivity, and have better mechanical properties and durability.

[0216] The present application also provides an inner cavity high porosity all-waste lightweight high-strength prefabricated building block, which comprises, by mass:

[0217] 20.6 parts of all-waste Alinite foamed cement slurry, 3.9 parts of waste glass powder, 3.2 parts of solid sulfur ash active powder, 1.3 parts of wheat husk ash, 34.9 parts of inner cavity high porosity lightweight artificial coarse aggregate, 24.8 parts of tailings sand fine aggregate, 8.1 parts of recycled glass fiber, 0.2 parts of water reducer, 3 parts of water, the tailings sand fine aggregate has a particle size of 0.125-2mm, the recycled glass fiber has a diameter of 0.35mm and a length of 6-14mm, and the water reducer is a polycarboxylic acid high-efficiency water reducer;

[0218] The particle size of the inner cavity high porosity lightweight artificial coarse aggregate is 5-40 mm, and it includes 20-30 parts of coal liquefaction heavy oil, 30-45 parts of fly ash, 5-10 parts of epichlorohydrin saponified waste residue powder, and 15-20 parts of coal gangue slurry below 4500 kcal.

[0219] In some embodiments, the all-waste alnitr foamed cement slurry includes, by weight, 66-69 parts of all-waste alnitr cement, 1.5-3.5 parts of sodium dodecylbenzene sulfonate, 0.1-0.5 parts of amino acid surfactant, 0.2-0.5 parts of hydroxypropyl cellulose, and 28-30 parts of water.

[0220] In some embodiments, the all-waste Alinite cement includes, by weight, 25-30 parts of blast furnace slag, 20-25 parts of phosphorus slag, 3-8 parts of furnace ash, 25-30 parts of fly ash, 5-10 parts of coal gangue powder, 6-9 parts of alkali slag, and 5-15 parts of desulfurized gypsum.

[0221] For specific embodiments, please refer to the above-mentioned embodiments 1 to 3, which will not be described in detail here.

[0222] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.

Claims

1. A hollow, high-porosity, all-waste, lightweight, high-strength prefabricated building block, characterized in that: In terms of mass fraction, it includes: 20.6 parts of all-waste Alinite foamed cement slurry, 3.9 parts of waste glass powder, 3.2 parts of solid sulfur ash active powder, 1.3 parts of wheat husk ash, 34.9 parts of inner cavity high porosity lightweight artificial coarse aggregate, 24.8 parts of tailings sand fine aggregate, 8.1 parts of recycled glass fiber, 0.2 parts of water reducer, 3 parts of water, the tailings sand fine aggregate has a particle size of 0.125-2mm, the recycled glass fiber has a diameter of 0.35mm and a length of 6-14mm, and the water reducer is a polycarboxylic acid high-efficiency water reducer; According to the mass percentage, the all-waste alinite foamed cement slurry includes 66-69 parts of all-waste alinite cement, 1.5-3.5 parts of sodium dodecylbenzene sulfonate, 0.1-0.5 parts of amino acid surfactant, 0.2-0.5 parts of hydroxypropyl cellulose, and 28-30 parts of water; According to the mass percentage, the all-waste Alinite cement includes 25-30 parts of blast furnace slag, 20-25 parts of phosphorus slag, 3-8 parts of furnace ash, 25-30 parts of fly ash, 5-10 parts of coal gangue powder, 6-9 parts of alkali slag, and 5-15 parts of desulfurized gypsum; The particle size of the inner cavity high porosity lightweight artificial coarse aggregate is 5-40 mm, and it includes 20-30 parts of coal liquefaction heavy oil, 30-45 parts of fly ash, 5-10 parts of epichlorohydrin saponified waste residue powder, and 15-20 parts of coal gangue slurry below 4500 kcal; The method for preparing the inner cavity high porosity lightweight artificial coarse aggregate comprises the following steps: S201, 20-30 parts of coal liquefaction heavy oil, 30-45 parts of fly ash and 5-10 parts of epichlorohydrin saponified waste residue powder are mixed to obtain a raw meal, and the raw meal is put into a granulator for spheroidization treatment, the granulator speed is 60-80 r / min, and raw meal balls are obtained, the fly ash particle size is 200-300 mesh, and the epichlorohydrin saponified waste residue powder particle size is 200-300 mesh; The raw material balls with particle sizes of 5mm, 10mm, 15mm, 20mm, 25mm, 30mm and 35mm are selected to enter the next process; S202, place 15~20 portions of coal gangue slurry below 4500 kcal in the central injection machine, and then place raw material balls with particle sizes of 5mm, 10mm, 15mm, 20mm, 25mm, 30mm, 35mm into the corresponding 10mm, 15mm, 20mm, 25mm, 30mm, 35mm, 40mm molds of the central injection machine for injection treatment: The coal gangue slurry with a pressure of less than 4500 kcal is hydraulically injected into the raw ball by a central injection machine to obtain the injected raw ball. The injection amount of the raw ball with a particle size of 5 mm is 0.02 mL, the injection amount of the raw ball with a particle size of 10 mm is 0.15 mL, the injection amount of the raw ball with a particle size of 15 mm is 0.5 mL, the injection amount of the raw ball with a particle size of 20 mm is 1.2 mL, the injection amount of the raw ball with a particle size of 25 mm is 2.4 mL, the injection amount of the raw ball with a particle size of 30 mm is 4 mL, and the injection amount of the raw ball with a particle size of 35 mm is 5.5 mL; Screen the injection raw material balls with particle sizes of 5mm<particle size≤10mm, 10mm<particle size≤15mm, 15mm<particle size≤20mm, 20mm<particle size≤25mm, 25mm<particle size≤30mm, 30mm<particle size≤35mm, 35mm<particle size≤40mm for standby use; S203, placing the pressed raw material balls obtained in step S202 in a compacting machine, setting the pressure value to 0.02-0.1 MPa, and performing spherical shaping and compacting of the aggregate to obtain compacted aggregate: The set pressure value for the pressed raw ball with a particle size of 5mm<particle size≤10mm is 0.1Mpa, the set pressure value for the pressed raw ball with a particle size of 10mm<particle size≤15mm is 0.09Mpa, the set pressure value for the pressed raw ball with a particle size of 15mm<particle size≤20mm is 0.08Mpa, the set pressure value for the pressed raw ball with a particle size of 20mm<particle size≤25mm is 0.07Mpa, the set pressure value for the pressed raw ball with a particle size of 25mm<particle size≤30mm is 0.05Mpa, the set pressure value for the pressed raw ball with a particle size of 30mm<particle size≤35mm is 0.03Mpa, and the set pressure value for the pressed raw ball with a particle size of 35mm<particle size≤40mm is 0.02Mpa; The compacted aggregate with a particle size of 5 to 40 mm is selected and sent to the next process; S204, placing the compacted aggregate obtained in S203 in a zoned temperature-controlled calcining device for microwave zoned multi-stage calcination: The compacted aggregate is microwave calcined at 400°C in the first zone for 20 minutes, then the compacted aggregate is microwave calcined at 700°C in the second zone for 15 minutes, and then the compacted aggregate is microwave calcined at 1000°C in the third zone for 10 minutes to obtain a molded aggregate; The formed aggregate is subjected to oxygen-free environment micro-carbon-fixing wind cooling to room temperature in the fourth zone of CO2 exhaust air cooling; Finally, the formed aggregate cooled to room temperature is placed in a 32-hedron vertex passivation blister steel ball electromagnetic shell solidification device with a diameter of 5 mm, and the outer shell of the formed aggregate cooled to room temperature is continuously solidified with small force and high frequency for 5 minutes to obtain a lightweight artificial coarse aggregate with high porosity in the inner cavity.

2. The inner cavity high porosity all-waste lightweight high strength prefabricated building block according to claim 1, characterized in that: The particle size distribution of the manufactured inner cavity high-porosity lightweight artificial coarse aggregate includes: 5 mm<particle size≤10 mm: 10~15%; 10 mm<particle size≤20 mm: 10~15%; 20 mm<particle size≤30 mm: 35~40%; 30 mm<particle size≤35 mm: 20~25%; 35 mm<particle size≤40 mm: 15%.

3. The inner cavity high porosity all-waste lightweight high strength prefabricated building block according to claim 1, characterized in that: The preparation method of the coal gangue slurry with a content of less than 4500 kcal comprises the following steps: Coal gangue powder with less than 4500 kcal and water are stirred in a mixer at a mass percentage ratio of 1.5-2 for 10-15 minutes to obtain coal gangue slurry with less than 4500 kcal. The mixer speed is 500-600 r / min, and the particle size of the coal gangue powder with less than 4500 kcal is 150-200 mesh.

4. The inner cavity high porosity all-waste lightweight high strength prefabricated building block according to claim 1, characterized in that: The coal liquefaction heavy oil has a specific gravity of 0.85-0.

9.

5. A method for preparing an inner cavity high porosity all-waste lightweight high-strength prefabricated building block, which is used to prepare an inner cavity high porosity all-waste lightweight high-strength prefabricated building block as claimed in any one of claims 1 to 4, characterized in that: It includes the following steps: S1. Provide mold: clean the inside of the 2000mm×1000mm×120mm mold and assemble it. Apply release agent after compaction; S2, 34.9 parts of high-porosity lightweight artificial coarse aggregate with internal cavity and 24.8 parts of tailings sand fine aggregate were placed in a mixer and stirred for 3 minutes at a speed of 120-150 r / min; S3, preparing all-waste alinite foamed cement slurry; S4, put 20.6 parts of all-waste Alinite foamed cement slurry, 3.9 parts of waste glass powder, 3.2 parts of fixed sulfur ash active powder, and 1.3 parts of wheat husk ash into a mixer according to the proportion and stir for 4 minutes, and the mixer speed is 120-150 r / min; S5. Mix 0.2 parts of water reducer with 3 parts of water, add into the mixer and stir for 2 minutes at a speed of 120-150 r / min. S6, adding 8.1 parts of recycled glass fiber into a mixer and stirring for 2 minutes at a mixer speed of 120-150 r / min; then stirring for 1 minute at a mixer speed of 250-300 r / min to obtain a lightweight concrete slurry; S7, laying the mold flat on the ground, pouring the lightweight concrete slurry into the mold, and performing vibration treatment to obtain initial setting concrete, the vibration time is 10-15s, the amplitude is 0.1-0.5mm, and the vibration frequency is 20-50Hz; S8. Curing the primary setting concrete: placing the primary setting concrete in an environment with a temperature of 20±2° C. and a relative humidity of 65-75% for 24 hours, then demoulding to obtain demoulding concrete, and curing the demoulding concrete for 7 days at a temperature of 20±2° C. and a relative humidity greater than 95%; after the demoulding concrete is completely solidified, curing it under natural conditions for 7 days to obtain a finished product with a high-porosity, fully-waste, lightweight, high-strength prefabricated block having a cavity.

6. The method for preparing the inner cavity high porosity all-waste lightweight high strength prefabricated building block according to claim 5, characterized in that: In S3, the method for preparing the all-waste Alnit foamed cement slurry comprises the following steps: Add 28-30 parts of water into a stirring pot, dissolve 1.5-3.5 parts of sodium dodecylbenzene sulfonate in the water, add 0.1-0.5 parts of an amino acid surfactant, and stir for 5-10 minutes to obtain a solution; The solution is placed in a mixer, and then 66-69 parts of all-waste alnit cement and 0.2-0.5 parts of hydroxypropyl cellulose are placed in the mixer and stirred for 5-10 minutes at a mixer speed of 500-600 r / min to obtain all-waste alnit foamed cement slurry.

7. The method for preparing the inner cavity high porosity all-waste lightweight high strength prefabricated building block according to claim 6, characterized in that: The method for preparing the all-waste alnit cement comprises the following steps: Grind 25-30 parts of blast furnace slag, 20-25 parts of phosphorus slag, 3-8 parts of furnace ash, 25-30 parts of fly ash, 5-10 parts of coal gangue powder, and 6-9 parts of alkali slag, pass through a 200-mesh sieve, mix evenly, and press into a test cake of 50 mm × 5 mm; The test cake is preheated at 800-1000° C. for 5-10 minutes, calcined at 1250-1300° C. for 40-60 minutes, and cooled to 30° C. to obtain cement clinker; The cement clinker is mixed with 5-15 parts of desulfurized gypsum and ground to a fineness of 400-500m 2 / kg, to obtain the all-waste alinite cement.

Citation Information

Patent Citations

  • Thermal insulation building block prepared from plant fiber modified spoil and preparation method of thermal insulation building block

    CN111099866A